The genera Luzonimyia and Pararhinoleucophenga from China (Diptera: Drosophilidae), with DNA barcoding information - Gao, Qingsong (Zootaxa, 2014)
Four new species are described from Yunnan, China, which belong to two different genera within the subfamily Steganinae: Luzonimyia hirsutina sp. nov., Luzonimyia setocauda sp. nov., Pararhinoleucophenga amnicola sp. nov. and Pararhinoleucophenga sylvatica sp. nov. The DNA sequences and GenBank accession numbers of the mitochondrial COI gene among Chinese species are provided.